IMPROVEMENT OF THE PATIENT CARE PROCESS BASED ON THE PRINCIPLES OF CLINICAL AUDIT - Gavrilyuk А.О.; Zharlinska, R.G.; Mishchuk А.А.; Vergeles К.М.; Berezovskyi А.М.; Pashynskyi Ya.М.; Iakovtsova І.I. (World of Medicine and Biology, 2020)
The purpose of the study was to analyse the possibilities of implementing a clinical audit in the activities of the health care institutions (HCI) and to summarize the steps taken during the audit. The article analyses modern approaches to clinical auditing and existing models based on the principles of the Deming - Shewhart cycle (PDCA). A standardized model of the patient’s clinical route based on the principles of clinical audit has been developed. The clinical route of the patient is differentiated into blocks that reflect the principle of optimal distribution of responsibilities among staff, which will improve the quality of patient care.